Ventricular tachycardia due to cardiac ischaemia: assessment by exercise electrocardiography. Issue 6139 (9th September 1978) - Talbot, Stephen; Kilpatrick, David; Krikler, Dennis; Oakley, Celia M
Abstract : Although ventricular tachycardia is a well-known complication of myocardial ischaemia and may be provoked by exercise, many patients may appreciate only the angina and be unaware of the unduly rapid heart rate that precipitates it. Exercise testing is needed to show this arrhythmia and to enable treatment to be started. Twenty-three patients were found to have chronic ischaemic heart disease complicated by ventricular tachycardia. Six patients with old myocardial infarction had ventricular tachycardia at rest which required conversion to sinus rhythm; 17 patients developed ventricular tachycardia only when they exercised. In 12 of these 17 patients coronary angiography showed disease of the anterior descending branch of the left coronary artery; other vessels were usually also affected. Although beta-adrenergic blocking drugs increased exercise tolerance, ventricular tachycardia still occurred when the heart rate on exercise reached a level similar to that before treatment. In five patients coronary artery bypass surgery was performed because of angina and exercise-induced ventricular tachycardia. Exercise tolerance was increased in all three patients who underwent exercise tests after operation, and in two of these patients, both of whom were known to have patent grafts, ventricular tachycardia was abolished. If part of the beneficial effect of coronary bypass surgery is preventing life-threatening ventricular arrhythmias it is essential to detect these, and ambulatory monitoring and stress testing have a complementary role.